Development of Basketball Game Modifications for Elementary Schools - Rahma Dewi; Bessy Sitorus Pane (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2022)
This study aims to develop a basketball game model for elementary schools. The model that was made beforehand was validated by 3 experts, 1 sports academic expert, 1 expert trainer and 1 referee expert. The small group test involved 6 elementary school children and the trial group involved 25 elementary school children. The basketball game model for elementary schools has been validated and results from expert validation that each model is valid and can be used as a basket play model for children, with a validity percentage of 76% -100%. The results of a small group test of 6 elementary school children showed that the basketball game model at the elementary school has met the reader properly or is valid. The percentage of validity of the questionnaire that was distributed to the sample showed that 91% -100% of them agreed with the ball game for schoolchildren. The percentage of validity from the questionnaire that was distributed to the sample shows that 87% - 97% of those who approve the game meet the criteria.